2012
DOI: 10.1016/j.jnutbio.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol up-regulates SIRT1 and inhibits cellular oxidative stress in the diabetic milieu: mechanistic insights

Abstract: Several lines of evidence support a role for oxidative stress in diabetic complications Diabetic patients have increased O2− production in monocytes. Loss of SIRT1 activity may be associated with metabolic diseases such as diabetes. Several studies have shown that SIRT1 can regulate mammalian FOXO transcription factors through direct binding and/or deacetylation. However, interactions between SIRT1 and FOXO under diabetic conditions are unclear. The phytochemical resveratrol, has recently gained attention for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 72 publications
6
74
0
3
Order By: Relevance
“…Upregulation of SIRT1 has also been shown to reduce cellular oxidative stress in the diabetic milieu (68). In this study, we attempted to expand the number of resveratrol derivatives by means of an enzymatic glycosylation approach that could help to generate novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of SIRT1 has also been shown to reduce cellular oxidative stress in the diabetic milieu (68). In this study, we attempted to expand the number of resveratrol derivatives by means of an enzymatic glycosylation approach that could help to generate novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has demonstrated that resveratrol exerts antioxidant effects via upregulation of SIRT1 expression [19]. Therefore, we examined whether resveratrol affected SIRT1 expression in adrenal glands during endotoxemia.…”
Section: Effects Of Lps and Resveratrol On Sirt1 Expression In Adrenamentioning
confidence: 94%
“…Resveratrol can increase the SIRT1 deacetylation activity, which reduces FOXO1 and FOXO3a acetylation and increases the nucleus localization, resulting stronger transcriptional activity. Resveratrol activates AMPK, which increases the deacetylase activity of SIRT1, and further increases the FOXO1 transcription activity (92,93). Studies have demonstrated that certain proteins form complexes with FOXO-SIRT1.…”
Section: Acetylation Of Foxo Proteinsmentioning
confidence: 99%